2017
DOI: 10.1002/dta.2305
|View full text |Cite
|
Sign up to set email alerts
|

PTCA (1H‐pyrrole‐2,3,5‐tricarboxylic acid) as a marker for oxidative hair treatment

Abstract: Hair analysis for the assessment of alcohol or drug abstinence has become a routine procedure in forensic toxicology. Hair coloration leading to loss of incorporated xenobiotics and to false negative results has turned out to be a major problem. Currently only colored extracts provide hints of manipulations but not bleaching. A liquid chromatographic-tandem mass spectrometric (LC-MS/MS) method was developed and validated to determine 1H-pyrrole-2,3,5-tricarboxylic acid (PTCA), a major oxidation product of mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 27 publications
(40 reference statements)
3
27
0
Order By: Relevance
“…Heavy-labeled and deuterated internal standards (IS) adenosine ribose-D 1 , arginine-13 C 6 , caffeine 3-methyl-13 C, carnitine trimethyl-D 9 , deoxycholic acid-D 4 , D-fructose 13 Venice bleaching oxidation powder) were purchased from DOBI (Suhr, Switzerland). Heavy-labeled and deuterated internal standards (IS) adenosine ribose-D 1 , arginine-13 C 6 , caffeine 3-methyl-13 C, carnitine trimethyl-D 9 , deoxycholic acid-D 4 , D-fructose 13 Venice bleaching oxidation powder) were purchased from DOBI (Suhr, Switzerland).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Heavy-labeled and deuterated internal standards (IS) adenosine ribose-D 1 , arginine-13 C 6 , caffeine 3-methyl-13 C, carnitine trimethyl-D 9 , deoxycholic acid-D 4 , D-fructose 13 Venice bleaching oxidation powder) were purchased from DOBI (Suhr, Switzerland). Heavy-labeled and deuterated internal standards (IS) adenosine ribose-D 1 , arginine-13 C 6 , caffeine 3-methyl-13 C, carnitine trimethyl-D 9 , deoxycholic acid-D 4 , D-fructose 13 Venice bleaching oxidation powder) were purchased from DOBI (Suhr, Switzerland).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…13 Within the present, preliminary study, the analysis of further eumelanin degradation products, their formation under different conditions and the applicability F I G U R E 3 Mean and SD (n = 3) of analyte peak area ratios (yaxis: Compound/sample weight) of PTCA, isoPTCA and PTeCA in dependence of increasing H 2 O 2 concentrations (1.9%, 3%, 6%, 9%, and 12%) and incubation times (15 min, 30 min, 60 min) (x-axis) (experiment 2) F I G U R E 2 Box plots for PTCA, isoPTCA, and PTeCA. Previous studies identified the eumelanin degradation product PTCA as a marker for oxidative hair treatment, however requiring the consideration of cut-off values.…”
Section: Targeted Analysis and Interpretation Of Ptca Isoptca Andmentioning
confidence: 99%
See 3 more Smart Citations